INNOVATIVE SOLUTIONS FOR REGULATING PEDESTRIAN AND VEHICLE FLOWS IN ARCHITECTURAL PROJECTS - Sh.A.Egamberdiyeva; D. A. Axmadjonova (Bright Mind Publishing, 2025)
This article is devoted to the study of innovative solutions for regulating pedestrian and vehicle flows in architectural projects. Managing traffic flows in urban spaces and building designs is of great importance, yet traditional approaches are often insufficiently effective. The research analyzes modern simulation and modeling techniques, as well as practical solutions applied in real architectural projects. The results demonstrate that innovative approaches enable safe, efficient, and convenient management of pedestrian and vehicle flows. Additionally, the article examines various innovative technologies, including smart signaling systems, interactive crossings, and flow optimization methods. The findings of this study can provide practical guidance for architects, urban planners, and transport engineers seeking to implement effective flow management strategies in modern architectural designs.
Keywords: Architectural projects, pedestrian flow, vehicle flow, innovative solutions, flow management, urban planning, smart technologies, safety, transport logistics, design optimization.